2019
DOI: 10.1596/1813-9450-9065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of International Scrutiny on Manufacturing Workers: Evidence from the Rana Plaza Collapse in Bangladesh

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies have shown how female workers withstand significantly lower working conditions compared to men (Barrientos 2019), while seniority, education, and age can also significantly influence access to labour entitlements (Huynh 2016;Węziak-Białowolska et al 2019;Bossavie et al 2020).…”
Section: Eswatini and Lesotho's Apparel Sectormentioning
confidence: 99%
“…Previous studies have shown how female workers withstand significantly lower working conditions compared to men (Barrientos 2019), while seniority, education, and age can also significantly influence access to labour entitlements (Huynh 2016;Węziak-Białowolska et al 2019;Bossavie et al 2020).…”
Section: Eswatini and Lesotho's Apparel Sectormentioning
confidence: 99%
“…As these policies have the stated objective to benefit worker welfare in sourcing markets, our analysis sets out to investigate this question theoretically and empirically. 4 Bossavie et al (2020) study the effects of improvements in Bangladeshi labor regulations after the factory collapse of Rana Plaza in 2013. Using a synthetic control approach, they find that working conditions improved whereas female wages decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Although this sector has immense contribution to economy, there are many problems associated with this sector which relate to the employees' social, housing, transport, safety and security issues. The safety issue that has generated a lot of attention in both the academia and media is workers' safety, especially building and fire safety, such as the collapse of Rana Plaza in 2013 [8]. However, the traffic safety of the employees is one major safety issue that has yet to receive sufficient attention in the work safety literature.…”
Section: Introductionmentioning
confidence: 99%